Pemanfaatan TTG Mesin Grinder dalam Proses Pengolahan Jagung Menjadi Menir untuk Meningkatkan Nilai Ekonomi Hasil Pertanian dan Peternakan Unggas - Yoto Yoto; Didik Nurhadi; Agus Suyetno; Putri Ardista Nursisda Mawangi; Muhammad Idris Effendi; Putrinda Inayatul Maula (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This community service program aims to improve the welfare of corn farmers and poultry farmers in Tempursari Village by providing appropriate technology in the form of a corn grinding machine. The main problem faced is the high price of animal feed, especially corn grits. Through observations and interviews, it was found that farmers and ranchers did not have the knowledge and access to corn milling technology. The service activities include training on the use of the grinding machine, demonstrations, and the handover of the machine to farmer groups. Evaluation results show that this machine can increase the efficiency of feed production, reduce production costs, and increase the added value of corn. The active participation of the community in the training shows their high enthusiasm for this new technology. In conclusion, this service program has successfully provided an effective solution to the problems faced by the people of Tempursari Village. The presence of the corn grinding machine is expected to increase the income of farmers and ranchers and contribute to the development of the agricultural sector in the area